Hubungan Pengetahuan dengan Perilaku Pencegahan Penyakit Menular Seksual (PMS) melalui Penggunaan Kondom pada Pekerja Seks Komersial (PSK) di Wilayah Mangga Besar Jakarta Pusat Tahun 2014 - Edward Syam (Lembaga Penelitian Universitas YARSI, 2017)
PSK is is one of the most vulnerable groups are infected with sexually transmitted diseases (STDS). The Mangga Besar of Central Jakarta is a spread of PSK and place a night club which allows the occurrence of free sex behaviour and ultimately at risk against STDS. The purpose of this research is to know the relationship of knowledge with the behavior prevention of STDS on commercial sex workers (PSK) in The Mangga Besar of Central Jakarta in 2014. The method in this research is a survey that uses Cross-sectional method. The subjects in the research were 253 workers of commercial sex in The Mangga Besar of Central Jakarta. Data analysis use Chi Square test. The results of the research is known significant (p value 0.011 and OR value 3.736) 60.7% of commercial sex workers who perform preventive of STDS as well. This study is health counselling about PMS, increasing confidence the PSK, post messages about health prevention of STDS, and support health workers against commercial sex workers.